Unique thermodynamic relationships for ΔfHo and ΔfGo for crystalline inorganic salts. I. Predicting the possible existence and synthesis of Na2SO2 and Na2SeO2. Addendum. Issue 6 (2nd December 2016) - Vegas, Ángel; Liebman, Joel F.; Jenkins, H. Donald Brooke
Abstract : Addendum toVegas et al. [(2012), Acta Cryst. B68, 511–527] . Abstract : Addendum toVegas et al. [(2012 ), Acta Cryst. B68, 511–527] .